Higher Precision in Pointing Movements of the Preferred vs. Non-Preferred Hand Is Associated with an Earlier Occurrence of Anticipatory Postural Adjustments - Bruttini, Carlo; Esposti, Roberto; Bolzoni, Francesco; Cavallari, Paolo (Frontiers in Human Neuroscience, 2016)
It is a common experience to exhibit a greater dexterity when performing a pointing movement with the preferred limb vs. the non-preferred one. Here we provide evidence that the higher precision in pointing movements of the preferred vs. non-preferred hand is associated with an earlier occurrence of the Anticipatory Postural Adjustments (APAs). In this aim, we compared the APAs which stabilize the left or the right arm when performing a pen-pointing movement (prime mover Flexor Carpi Radialis). Moreover, we analysed the elbow and wrist kinematics as well as the precision of the pointing movement. The mean kinematics of wrist movement and its latency, with respect to prime mover recruitment, were similar in the two sides, while APAs in Triceps Brachii, Biceps Brachii and Anterior Deltoid were more anticipated when movements were performed with the preferred than with the non-preferred hand (60-70 vs. 20-30 ms). APAs amplitudes were comparable in the muscles of the two sides. Earlier APAs in the preferred limb were associated with a better fixation of the elbow, which showed a lower excursion, and with a less scattered pointing error (preferred: 10.1 ± 0.8 mm; non-preferred: 16.3 ± 1.7). Present results suggest that, by securing the more proximal joints dynamics, an appropriate timing of the intra-limb APAs is necessary for refining the voluntary movement precision, which is known to be scarce on the non-preferred side.